2022
DOI: 10.1186/s40580-022-00334-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pt grain size on ferroelectric properties of zirconium hafnium oxide by chemical solution deposition

Abstract: The effects of the grain size of Pt bottom electrodes on the ferroelectricity of hafnium zirconium oxide (HZO) were studied in terms of the orthorhombic phase transformation. HZO thin films were deposited by chemical solution deposition on the Pt bottom electrodes with various grain sizes which had been deposited by direct current sputtering. All the samples were crystallized by rapid thermal annealing at 700 °C to allow a phase transformation. The crystallographic phases were determined by grazing incidence X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…This seminal study not only underscores the pivotal role played by heterogeneous metal interfaces, particularly Cu, in anode-free ZIBs but also underscores the critical significance of the microscopic attributes of these metal interfaces in determining the ZIBs performance. For metal materials, the grain size, crystal orientation, and texture properties have different effects on their own performance indexes, so it is particularly important to study their effects in the anode-free application of zinc ion batteries.…”
Section: Introductionmentioning
confidence: 99%
“…This seminal study not only underscores the pivotal role played by heterogeneous metal interfaces, particularly Cu, in anode-free ZIBs but also underscores the critical significance of the microscopic attributes of these metal interfaces in determining the ZIBs performance. For metal materials, the grain size, crystal orientation, and texture properties have different effects on their own performance indexes, so it is particularly important to study their effects in the anode-free application of zinc ion batteries.…”
Section: Introductionmentioning
confidence: 99%
“…The optimization process of multiferroic heterostructures of our interest, based on bilayer systems of ferromagnetic materials such as the hexaferrite BaFe 12 O 19 and ferroelectric materials such as LuFeO 3 and YbFeO 3 , crucially requires first a high-quality bottom electrode, which remains stable at elevated growth temperatures Tg > 900 °C in an oxidizing atmosphere during the pulsed laser deposition (PLD) growth of the above-mentioned subsequent layers [ 1 , 2 , 3 , 4 , 5 ]. Platinum is one of the noble metals, and is widely used in the application field of metal-ferroelectric-metals (MFMs) [ 6 , 7 , 8 ], ferroelectric memories [ 9 ], and microelectromechanical systems (MEMSs) [ 10 ] due to its high melting point, inertness in hard atmospheres, and low resistivity. Several studies have reported the effects of the structure and morphology of the bottom electrode on the performance of ferroelectric films and MEMSs [ 7 , 8 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…[5] Otherwise, it will be retained. Ferroelectric-based components including ferroelectric capacitor, [6][7][8][9][10][11][12] ferroelectric random-access memory (FeRAM), [13][14][15] ferroelectric field effect DOI: 10.1002/smll.202305271 transistor (FeFET), [16][17][18][19][20][21][22] ferroelectric diode (Fe-Diode), [23][24][25] and ferroelectric tunnel junction (FTJ) are also thought to be viable options for low-power non-volatile memory with two stable states.…”
Section: Introductionmentioning
confidence: 99%